Analysis of the Calculation of a Plasma Sheath Using the Parallel SO-DGTD Method - Qian Yang; Bing Wei; Linqian Li; Debiao Ge (International Journal of Antennas and Propagation, 2019)
The plasma sheath is known as a popular topic of computational electromagnetics, and the plasma case is more resource-intensive than the non-plasma case. In this paper, a parallel shift-operator discontinuous Galerkin time-domain method using the MPI (Message Passing Interface) library is proposed to solve the large-scale plasma problems. To demonstrate our algorithm, a plasma sheath model of the high-speed blunt cone was established based on the results of the multiphysics software, and our algorithm was used to extract the radar cross-section (RCS) versus different incident angles of the model.